Réponses

2014-10-10T20:37:39+02:00


A = 15x - (x + 7)²

A = 15x - x² + 2 × 7 × x + 7²

A = 15x - x² + 14x + 49

A = -x² + 29x + 49


B = x (x - 1) - (x - 2)²

B = x² - x - ( x² - 2 × x × 2 - 2²)

B = x² - x - ( x² - 4x - 4)

B = x² - x - x² + 4x + 4

B = 3x + 4


C = (x - 2) (x + 2) - (x + 1)²

C = x² - 2² - (x² + 1 × x × 2 + 1²)

C = x² - 4 - (x² + 2x + 1)

C = x² - 4 - x² - 2x - 1

C = - 2x - 5

MERCI BEAUCOUP !!!!!!!!!!!!
derien :)
B= -3x+4
Non
2014-10-10T23:12:42+02:00
À= 15x-(x²+14x+49)=15x-x²-14x-49=-x²+x-49

B= x²-x-(x²-4x+4)=x²-x-x²+4x-4=3x-4

C= x²-4-(x²+2x+1)=x²-4-x²-2x-1=-2x-5